Visual function and quality of life after cataract surgery in older adults at the National Hospital Pnp “Luis N. Sáenz” - Tello Arquíñego, Johans Neil (2024)
Objective: Determine the visual perception and quality of life in older adults undergoing bilateral cataract surgery at the National Hospital PNP “Luis N. Sáenz”. Method: It is a descriptive, retrospective, cross-sectional investigation, the population being older adults who underwent bilateral cataract surgery. The instruments used were the Visual Function Index and Vision Related Quality of Life Questionnaire -VisQol-15 and the Quality of Life and Level of Independence Questionnaire for carrying out Activities of Daily Living -Katz Index, both instruments, validated by the National Eye Institute. Results: The postoperative visual perception was good, with a large majority of the population obtaining very good Visual Function and Visual Acuity. In addition, the post-surgical results indicate that the perception of quality of life is very positive, with the entire population showing a total absence or a slight inability to carry out their daily activities. It was also observed that the highest percentage of individuals affected by this pathology are between 60 and 70 years old, still being part of the economically active population, so visual rehabilitation produced a very positive impact. Conclusions: Cataract surgery provides great visual rehabilitation, which is evidenced by an improvement in the perception of visual function and quality of life of postoperative patients.